Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 5 - Section 5.5 - Solving Equations by the Zero-Factor Property - 5.5 Exercises: 22

Answer

$x=\left\{ -2,2 \right\}$

Work Step by Step

$\bf{\text{Solution Outline:}}$ Express the given equation, $ -2x^2+8=0 ,$ in factored form. Then, use the Zero-Factor Property by equating each factor to zero. Finally, solve each equation. $\bf{\text{Solution Details:}}$ The factored form of the equation above is \begin{array}{l}\require{cancel} -2(x^2-4)=0 \\\\ -2(x+2)(x-2)=0 \\\\ \dfrac{-2(x+2)(x-2)}{-2}=\dfrac{0}{-2} \\\\ (x+2)(x-2)=0 .\end{array} Equating each factor to zero (Zero-Factor Property), then \begin{array}{l}\require{cancel} x+2=0 \text{ OR } x-2=0 .\end{array} Using the properties of equality to solve each of the equation above results to \begin{array}{l}\require{cancel} x+2=0 \\\\ x=-2 \\\\\text{ OR }\\\\ x-2=0 \\\\ x=2 .\end{array} Hence, the solutions are $ x=\left\{ -2,2 \right\} .$ $\bf{\text{Supplementary Solution/s:}}$ Factoring the negative $GCF= -2 ,$ the expression, $ -2x^2+8 ,$ above is equivalent to \begin{array}{l}\require{cancel} -2 \left( \dfrac{-2x^2}{-2}+\dfrac{8}{-2} \right) \\\\= -2 \left( x^2-4 \right) .\end{array} Using the factoring of the difference of $2$ squares which is given by $a^2-b^2=(a+b)(a-b),$ the expression above is equivalent to \begin{array}{l}\require{cancel} -2 \left( x+2 \right)\left( x-2 \right) .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.